Association of lipoprotein(a) levels with all-cause mortality following percutaneous coronary intervention. (3rd October 2022) - Dykun, I; Hendricks, S; Babinets, O; Al-Rashid, F; Totzeck, M; Rassaf, T; Mahabadi, A A
Abstract: Background: Although lipoprotein(a) (Lp(a)) is a causal genetic risk factor for atherosclerotic cardiovascular disease, the prognostic value of elevated Lp(a) in coronary artery disease (CAD) patients is inconsistent in previous studies. The precise impact of Lp(a) itself on all-cause mortality in addition to the changes in low-density lipoprotein cholesterol (LDL-C) levels remains uncertain. Purpose: We tested the hypothesis that Lp(a) levels in CAD patients is associated with long-term mortality, and such an association can by modified by LDL-C levels. Methods: The present analysis is based on the longitudinal ECAD registry of consecutive patients undergoing coronary angiography with percutaneous revascularization therapy at the West German Heart and Vascular Center between 2004 and 2019. Lp(a) was quantified at hospital admission using a particle-enhanced immunonephelometric method. The incidence of death due to any cause was evaluated during follow-up. Cox regression analysis was used to determine the association between Lp(a) and all-cause mortality, adjusting for age, sex, LDL-C, smoking status, and family history of premature cardiovascular disease. Results: Among 4941 patients (mean age 66.4±11.5 years, 77.8% male), median Lp(a) was 16 (7; 56) mg/dL and 1817 (36.8%) patients had elevated Lp(a) levels (≥30 mg/dl). During a median follow-up 3.1 years, 604 patients (12.2%) died. In multivariable Cox regression analysis, elevated Lp(a) was associated with an increased risk of all-cause mortality (Hazard ratio (HR): 1.23, [95% confidence interval (CI): 1.04; 1.45] p=0.01). When stratified by LDL-C category, only patients with LDL-C ≥100 mg/dL showed a significant association between Lp(a) and higher all-cause mortality (HR: 1.47; [1.16, 1.19], p<0.001), whereas Lp(a) levels were not linked with adverse prognosis, if LDL was better controlled (LDL<100mg/dl: 1.00; [0.79, 1.26], p=0.98). Conclusions: In a large longitudinal registry cohort of patients with CAD undergoing invasive coronary angiography, elevated Lp(a) was associated with increased long-term mortality. LDL-C control seem to interact with the impact of Lp(a) levels on the patient's prognosis following percutaneous revascularization therapy. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only.